PEREKAT KAYU LAPIS DARI DAUN LAMTORO (Leucaena Leucocephala) - Meldia Fitri (Jurnal Sains dan Teknologi: Jurnal Keilmuan dan Aplikasi Teknologi Industri, 2016)
Adhesives ( adesive ) is a very important material in the plywood industry, the amount of adhesives commonly used in the industry is an adhesive containing chemicals Urea formaldehyde . Urea Formaldehyde is a chemical compound which, when exposed to heat slightly will cause emissions which produce toxic gases that can pollute the air and cause health problems , can cause respiratory irritation and may even cause cancer .As a substitute for urea formaldehyde can be used natural materials containing tannin , tannin is widely available in a variety of plants , tannin present in the stems , bark , leaves and roots of plants. Manufacture of plywood adhesive of the leaf lamtoro besides environmentally friendly , can also increase the economic value of the leaves lamtoro .The process of making plywood adhesive of the leaf lamtoro by means of extraction with water at a temperature of 70 ° C for 2-5 hours , the adhesive quality test results are as follows : pH 6.8 ; Viscosity (thickness ) 1973.72 cps , density 1.0761 g / ml ; Test appearance ( color adhesive greenish brown , the smell is not overpowering ; does not appear any other materials that affect the adhesive ; content of 21.77 % solids ; gelatinasi time 39 minutes ; strong bonding strength ; the shelf life of one month. The cost of production of plywood adhesives of leaves lamtoro Rp.20.788.322 - with a production capacity of 1100 kg , in order to obtain the production cost of Rp.18 898,- /kg sticking plywood of leaves lamtoro . Keywords: Adhesives, Leaf lamtoro, manufacturing process, quality, cost of production.